Morphological and Molecular Characterization of Orchid Fruit Development - Dirks-Mulder, Anita; Ahmed, Israa; uit het Broek, Mark; Krol, Louie; Menger, Nino; Snier, Jasmijn; van Winzum, Anne; de Wolf, Anneke; van't Wout, Martijn; Zeegers, Jamie J.; Butôt, Roland; Heijungs, Reinout; et al. (Frontiers in Plant Science, 2019)
Efficient seed dispersal in flowering plants is enabled by the development of fruits, which can be either dehiscent or indehiscent. Dehiscent fruits open at maturity to shatter the seeds, while indehiscent fruits do not open and the seeds are dispersed in various ways. The diversity in fruit morphology and seed shattering mechanisms is enormous within the flowering plants. How these different fruit types develop and which molecular networks are driving fruit diversification is still largely unknown, despite progress in eudicot model species. The orchid family, known for its astonishing floral diversity, displays a huge variation in fruit dehiscence types, which have been poorly investigated. We undertook a combined approach to understand fruit morphology and dehiscence in different orchid species to get more insight into the molecular network that underlies orchid fruit development. We describe fruit development in detail for the epiphytic orchid species Erycina pusilla and compare it to two terrestrial orchid species: Cynorkis fastigiata and Epipactis helleborine. Our anatomical analysis provides further evidence for the split carpel model, which explains the presence of three fertile and three sterile valves in most orchid species. Interesting differences were observed in the lignification patterns of the dehiscence zones. While C. fastigiata and E. helleborine develop a lignified layer at the valve boundaries, E. pusilla fruits did not lignify at these boundaries, but formed a cuticle-like layer instead. We characterized orthologs of fruit-associated MADS-domain transcription factors and of the Arabidopsis dehiscence-related genes INDEHISCENT (IND)/HECATE 3 (HEC3), REPLUMLESS (RPL) and SPATULA (SPT)/ALCATRAZ (ALC) in E. pusilla, and found that the key players of the eudicot fruit regulatory network appear well conserved in monocots. Protein-protein interaction studies revealed that MADS-domain complexes comprised of FRUITFULL (FUL), SEPALLATA (SEP) and AGAMOUS (AG) /SHATTERPROOF (SHP) orthologs can also be formed in E. pusilla, and that the expression of HEC3, RPL and SPT can be associated with dehiscence zone development similar to Arabidopsis. Our expression analysis also indicates differences, however, which may underlie fruit divergence.